Can Shareholders Be at Rest after Adopting Clawback Provisions? Evidence from Stock Price Crash Risk - Bao, Dichu; Fung, Simon Yu Kit; Su, Lixin (Nancy) (Contemporary Accounting Research, 2018)
Abstract Using a propensity score matched sample and a difference‐in‐differences research design, we find that stock price crash risk increases after a firm voluntarily incorporates clawback provisions in executive officers' compensation contracts. This heightened crash risk is concentrated in adopters that increase upward real activities‐based earnings management and those that reduce the readability of 10‐K reports. Based on cross‐sectional analyses, we also find that the increased crash risk is more pronounced for adopters with high ex ante fraud risk, low‐ability managers, high CEO equity incentives, and low dedicated institutional ownership. Collectively, our results suggest that the clawback adoption per se does not curb managerial opportunism but rather induces managers to use alternative channels for concealing bad news, which may contribute to a greater stock price crash risk; and the increase in crash risk is more likely in cases where incentives are strong or monitoring is weak. Our results should be of interest to regulators and policymakers considering the effects of clawback adoption on the investing public.